Experimental design approach to COD and color removal of landfill leachate by the electrooxidation process - Sevil Veli (Elsevier, 2021)
Toxic leachates originate from landfills are one of the major environmental problems. It has an important role in groundwater contamination and its treatment is crucial for environmental protection. In this research, the Electrooxidation (EO) process is applied to the landfill leachate balancing pool effluent. At the beginning of the study, conventional characterization of landfill leachate was conducted. Then, the EO process was progressed via 14 stainless steel and parallel positioned electrodes. Through the Response Surface Methodology (RSM), the effectiveness of process variables was explained statistically. Effects of pH, current density, and reaction time on the process efficiency were studied and optimum conditions of the EO reaction were determined via COD and color removal efficiency parameters. By the model, optimum conditions of the reaction were found to be pH 7, current density 4.30 mA/cm2, and reaction time 35 min. The estimated removal efficiencies for COD and color were 42% and 97%, respectively. R2 values of the models were 98% for color removal and 93% for COD removal.